DI-086 Progressive multifocal leukoencephalopathy associated with fingolimob use in a patient with multiple sclerosis without previous exposure to immunosupressant drugs. (14th February 2016) - Calzado, G; Virgós, T; Bullejos, M; Gonzalez, G; Gonzalez, J; Garcia, G; Nazco, J
Abstract : Background: Fingolimod (Gilenya) is an immunomodulator which alters the immune system to reduce inflammation. It has been shown to benefit patients with relapsing forms of multiple sclerosis (MS). Progressive multifocal leukoencephalopathy (PML) is a serious brain infection caused by the John Cunningham (JC) virus. In August 2015, the US Food and Drug Administration (FDA) announced that a case of definite PML and a case of probable PML had been reported in MS patients taking fingolimod. One of these two cases is described here. It was reported to our reference pharmacovigilance centre and then to the US FDA. Purpose: To report a case of PML associated with fingolimod use. Material and methods: The patient was a 54-year-old man diagnosed with MS in 2002 and treated with interferon beta-1b. In 2012, after neurological evaluation, he began a secondline of treatment with fingolimod 0.5 mg/24 h. He was also taking mesalazine and pitavastatine for ulcerative colitis; none of these drugs are linked to PML. In 2015, the patient was hospitalised with suspected PML after developing new symptoms, including gait instability, clumsiness, inattention, somnolence and mental sluggishness. Fingolimod was discontinued. Results: He was diagnosed with PML based on symptoms, MRI findings and positive JC virus test in CSF. Mefloquine, mirtazapine and cidofovir/probenecib were prescribed to treat PML. Conclusion: This is one of very few cases of PML reported worldwide in patients taking fingolimod with no prior exposure to an immunosuppressant drug for MS or any other medical condition. However, no definitive causal relation between fingolimod and PML has been established. It was classified as conditional using the Karsch-Lasagna algorithm. No conflict of interest.